Tetrakis[μ-N,N′-bis(4-bromophenyl)formamidinato-κ2 N:N′]dimolybdenum(II) tetrahydrofuran solvate - Han, L.-J. (International Union of Crystallography, 2011)
The title complex, [Mo2(C13H9N2Br2)4]·C4H8O, contains a quadruply bonded Mo2 4+ unit equatorially coordinated by four N,N′-bis(4-bromophenyl)formamidinate ligands, forming a dimetal paddlewheel complex. The centroid of the Mo—Mo bond is located on a special position with 2/m symmetry. In the crystal, complex molecules are linked by Br⋯Br interactions [3.7049 (10) Å]. The disordered solvent molecule could not be satisfactorily modelled and was therefore eliminated from the final refinement.